2017
DOI: 10.1007/s10792-017-0486-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iris registration on visual outcome in wavefront-guided LASEK for myopic astigmatism

Abstract: IR had similar outcomes to conventional trackers in wavefront-guided LASEK, with less tendency of inducing coma, especially in higher myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Overall, results for both IR and NO IR appear better in the current study. Lee et al 11 compared the clinical outcomes after laser epithelial keratomileusis (LASEK) using the VISX Star S4 with and without IR in a small group of patients. The authors reported no significant differences in refractive outcomes between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, results for both IR and NO IR appear better in the current study. Lee et al 11 compared the clinical outcomes after laser epithelial keratomileusis (LASEK) using the VISX Star S4 with and without IR in a small group of patients. The authors reported no significant differences in refractive outcomes between the groups.…”
Section: Discussionmentioning
confidence: 99%